Challenges Facing Asian Sex Workers in Western Australia: Implications for Health Promotion and Support Services - Selvey, Linda A.; Lobo, Roanna C.; McCausland, Kahlia L.; Donovan, Basil; Bates, Julie; Hallett, Jonathan (Frontiers in Public Health, 2018)
Introduction: Asian sex workers are a significant part of the Australian sex industry. Criminal laws, racism, isolation, poor English language skills and stigma and discrimination combine to increase the vulnerability of Asian sex workers in Australia. To inform service delivery and potential legislative reform, we undertook a study of sex worker health and safety in Western Australia with a focus on Asian sex workers. Methods: This was a mixed methods study in which peer researchers played an essential role. We undertook a survey (available online and in paper form and translated into three languages other than English), semi-structured interviews with sex workers, and interviews with key advisors. Results: In our study, Asian sex workers were older, had lower levels of education, more likely to have sex work as their main source of income, work longer hours and work exclusively in a shop-front massage parlor compared to their non-Asian counterparts. The vast majority of Asian sex workers in our study said they had poor English language skills and the greatest proportion spoke Chinese languages. Sex work had a positive impact on the well-being of many respondents, and their level of psychological distress was similar to the general Australian population. Stress and “bad clients” were common negative impacts of sex work. Asian study participants were less likely than their non-Asian counterparts to smoke, undertake risky drinking or use illicit drugs. A similar proportion of Asian sex workers reported being assaulted compared to their non-Asian counterparts. Discussion/Conclusion: The major challenges facing Asian sex workers in WA seem to be stigma and discrimination, stress, social isolation, and confusion about their legal standing leading to a fear of authorities, particularly the police. Our findings support the need for enhanced targeted peer-based health promotion outreach services for Asian sex workers, increased Asian language services in sexual health clinics and decriminalization of sex work.